Entrepreneurial Intentions from an Entrepreneurial Knowledge Perspective, Mediating Subjective Norms Moderates Self-Efficacy - Kurjono; Sulthan Yusuf Abdullah (Economics Education Department Universitas Negeri Semarang, 2024)
This research aims to determine the influence of entrepreneurial knowledge on entrepreneurial intentions with the mediation of subjective norms and moderation of self-efficacy. This research is quantitative, analyzing responses to questionnaires distributed to 218 accounting education students at seven universities in Indonesia. Verify the data by hypothesis testing, then the collected data is analyzed using Partial Least Square -Structural Equation Modeling (PLS-SEM). The results of this research are that subjective norms perfectly mediate the influence of entrepreneurial knowledge on entrepreneurial intentions, but self-efficacy does not moderate the influence of entrepreneurial knowledge on entrepreneurial intentions. These results have implications to increase students' entrepreneurial intentions, the authorities should create course programs recommended by the business and industrial world, whether run by the government or the private sector. In addition, it is necessary to evaluate the entrepreneurship learning curriculum in order to increase the content of attitudes and capable beliefs. The originality of this research explores the entrepreneurial intentions of accounting education students in Indonesia. This research combines a mediation model and a moderation model.